Inactivation of LPS and RNase A on photocatalytically active surfaces - Kurz, Jochen; Eberle, Florian; Graumann, Tobias; Kaschel, Mariel-Esther; Sähr, Aline; Neumann, Frank; Dalpke, Alexander; Erdinger, Lothar (Chemosphere, 2011)
TiO2 coated surfaces are able to generate highly reactive oxidizing species under mild UV-A light exposure in the presence of water and oxygen. We have demonstrated that these radicals are sufficient to eliminate different pathogenic bacteria, by breaking their cell walls. The photocatalytic activity of surfaces coated with titanium dioxide offers therefore an alternative possibility of disinfection. However, restriction of bacterial growth does not protect surfaces from bacterial derived contaminations, such as endotoxins. Lipopolysaccharides (LPS) and Ribonuclease A (RNAse A) represent the two most abundant contaminations, causing severe problems in biomedical and immunological research as well as in the pharmaceutical industry. Due to their high stability, complete removal of these contaminants is technically challenging. Using irradiated TiO2 coated glass plates, RNAse A and LPS containing contaminations could be completely inactivated. By establishing highly sensitive immuno-based assays, destruction of the contaminants was quantified and shown to be independent of the initial concentrations, following a zero-order reaction. Exposure for 96h resulted in a reduction of 11ng of LPS and 7 units of RNase A cm−2 surface. These amounts are comparable to contamination levels found under standard working conditions. Titanium dioxide coatings provide therefore a powerful tool for auto-disinfection and self-cleaning of surfaces.
Gesehen am 11.07.2022